Transcriptome Analysis Reveals an Inhibitory Effect of Dihydrotestosterone-Treated 2D- and 3D-Cultured Dermal Papilla Cells on Hair Follicle Growth - Zhang, Yufan; Huang, Junfei; Fu, Danlan; Liu, Zhen; Wang, Hailin; Wang, Jin; Qu, Qian; Li, Kaitao; Fan, Zhexiang; Hu, Zhiqi; Miao, Yong (Frontiers in Cell and Developmental Biology, 2021)
Dermal papillae are a target of androgen action in patients with androgenic alopecia, where androgen acts on the epidermis of hair follicles in a paracrine manner. To mimic the complexity of the dermal papilla microenvironment, a better culture model of human dermal papilla cells (DPCs) is needed. Therefore, we evaluated the inhibitory effect of dihydrotestosterone (DHT)-treated two-dimensional (2D)- and 3D-cultured DPCs on hair follicle growth. 2D- and 3D-cultured DPC proliferation was inhibited after co-culturing with outer root sheath (ORS) cells under DHT treatment. Moreover, gene expression levels of β-catenin and neural cell adhesion molecules were significantly decreased and those of cleaved caspase-3 significantly increased in 2D- and 3D-cultured DPCs with increasing DHT concentrations. ORS cell proliferation also significantly increased after co-culturing in the control-3D model compared with the control-2D model. Ki67 downregulation and cleaved caspase-3 upregulation in DHT-treated 2D and 3D groups significantly inhibited ORS cell proliferation. Sequencing showed an increase in the expression of genes related to extracellular matrix synthesis in the 3D model group. Additionally, the top 10 hub genes were identified, and the expression of nine chemokine-related genes in DHT-treated DPCs was found to be significantly increased. We also identified the interactions between transcription factor (TF) genes and microRNAs (miRNAs) with hub genes and the TF–miRNA coregulatory network. Overall, the findings indicate that 3D-cultured DPCs are more representative of in vivo conditions than 2D-cultured DPCs and contribute to our understanding of the molecular mechanisms underlying androgen-induced alopecia.